A tiny lesion arising within Barrett’s esophagus - Francesco Pugliese,; Giulia Bonato,; Lorenzo Dioscoridi,; Marcello Cintolo,; Maria Costanza Aquilano,; Edoardo Forti,; Aurora Giannetti,; Angelo Italia,; Massimiliano Mutignani, (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Pugliese F, Bonato G, Dioscoridi L, et al. A tiny lesion arising within Barrett’s esophagus. Turk J Gastroenterol 2020; 5: 410-2.